آراء الإمام البوني في باب البيوع من خلال شرحه على الموطأ جمعا ودراسة - - المطنش, سامي; - غندير, عبد الباسط; اليمان, عنتر (University of Eloued-جامعة الوادي, 2017)
تناكلت ىذه ات١ذكرة موضوع آراء الإما البوني بُ باب البيوع من خلبؿ شرحو على ات١وطأ ػ تٚعا كدراسة ػ كىو تْث يكشف عن أت٫ية مكانة البوني ػ رتٛو الله ػ عند أىل العلم سواء بُ ات١ذىب ات١الكي الذم ينسب إليو أ بُ غتَه من ات١ذاىب كإبراز آراءه بُ البيوع، كمن أجل ذلك قسمنا تْثنا ىذا إبٔ مقدمة كمبحثتُ كخات٘ة، حيث أشرنا بُ ات١قدمة إبٔ أت٫ية دراسة موضوع البيوع بُ كقتنا اتٟابٕ، كتناكلنا بُ ات١بحث الأكؿ ترتٚة للئما البوني من حياتو كنسبو كشيوخو كتلبميذه كغتَىا، كتناكلنا أيضا بُ نفس ات١بحث نبذة عن كتاب تفستَ ات١وطأ للبوني، كتناكلنا بُ ات١بحث الثالث آراء الإما البوني بُ باب البيوع كبيع العرباف كالعينة كالربا كات١صراة كغتَىا من البيوع، كختمنا تْثنا تٓات٘ة تناكلت أىم النتائج التي استخلصناىا من البحث، كبُ الأختَ ذيلنا البحث بفهارس. Reserch Summary: The note addressed the subject of reviews front pony sales section by explaining the muwatta. collection and study. A search reveals the importance of niche alboni-Allah's mercy-scholars both in Maliki or other doctrines and highlighting. views on sales, and for that we divide our introduction and two sections and a conclusion,As we pointed out in the introduction to the importance of studying the subject of sales of our time.And we ate in the first episode of his life and alboni ahead translations ratio and ageing and his disciples and others, and also in the same episode about a book interpreting muwatta of Bonnie, we ate in the third section reviews the front pony sales section, such as the sale and sample could Arab masturbation and other sales, we sealed our main findings covered finale learned from research, and eventually our tail search indexes.
مذكرة ليسانس
Keywords: الامام البوني /البيوع /الموطأ; Imam Al-Buni / Al-Baya' / Al-Muwatta